An Investigation into the Determinants of Risk Disclosure in Banks: Evidence from Financial Sector of Pakistan - Ashfaq, Khurram; Zhang, Rui; Munaim, Abdul; Razzaq, Naveed (International Journal of Economics and Financial Issues, 2016)
The purpose of this paper is to find the determinants of quantity as well as quality of the risk disclosures in annual reports of banking sector of Pakistan. The paper employs the word count approach to measure the quantity of risk disclosures in annual reports whereas to measure the risk disclosure quality, risk disclosure quality index (RDQI) is adapted from the study by Barakat & Hussainey in 2013 after making some changes. The researcher selected a data sample on desired variables for a period of 7 years (2008-2014) through 31 scheduled banks (excluding 7 Foreign Banks) and run generalized least square as the researcher supposed there was an effect of endogeneity in the model. The researcher found confirmation that, banks with a higher proportion of independent non executive board directors, lower ownership proportion of executive management, banks with a high asset value and banks having non-governmental ownership tend to present to their stakeholders a higher degree of risk disclosure in terms of volume of information as well as quality of the disclosure. Practically, the results recommend that there should be strict regulations by the supervisory body to enhance the quantity and quality of risk disclosure by banks in their annual reports. Further, Audit committees of the banking institutions should positively play their vital role in this regard. As another practical suggestion, the findings demonstrate that banking institutions operating in Pakistan may improve their own risk disclosure quality and quantity by appointing independent outside board directors and ensuring the audit committee activities as effective monitors of risk disclosure and advisors for risk disclosure management at bank level. Keywords: Risk disclosure quality, Agency theory, corporate governance, Risk management. JEL Classification: M40